Co-Movement of Digital Currencies and Asian Stock Indexes: A Wavelets Based Multiresolution Analysis - Laraib, Muhammad; Siddiqui, Ammar Ahmed; Kaiser, Syed Najeeb Ullah (iRASD Journal of Economics, 2023)
The paper examines the co-movement relationship between Cryptocurrency and Asian major indices through Wavelet Coherence multiresolution technique and the Granger causality for result robustness. The indices data of Singapore and Japan stock market was used from January 2018 to December 2022, the outcome of our study shows great of co-relationship in the movement between Asian two major listed equity market indices and Cryptocurrencies investments. Moreover, the study shows that Japan stock market found to be more positively correlated with existing cryptocurrencies in comparison to Singapore stock market.